2020
DOI: 10.11591/ijai.v9.i1.pp81-90
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning based technique for plagiarism detection: a comparative study

Abstract: <table width="0" border="1" cellspacing="0" cellpadding="0"><tbody><tr><td valign="top" width="593"><p>The ease of access to the various resources on the web-enabled the democratization of access to information but at the same time allowed the appearance of enormous plagiarism problems. Many techniques of plagiarism were identified in the literature, but the plagiarism of idea steels the foremost troublesome to detect, because it uses different text manipulation at the same time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
7
0
5
Order By: Relevance
“…5-Word2Vec: is consider a deep learning-based predictive model within the category of unsupervised models that is used to compute and create high-quality dense, distributed. Words are represented as continuous vectors that capture contextual and semantic similarities [61]. 6-AUR-BoW: When user comments are broken into sentences, most user comments are too short, therefor when text is categorized, the text of the workbook is too short.…”
Section: -3 Text Vectorization Models and Feature Extractionmentioning
confidence: 99%
“…5-Word2Vec: is consider a deep learning-based predictive model within the category of unsupervised models that is used to compute and create high-quality dense, distributed. Words are represented as continuous vectors that capture contextual and semantic similarities [61]. 6-AUR-BoW: When user comments are broken into sentences, most user comments are too short, therefor when text is categorized, the text of the workbook is too short.…”
Section: -3 Text Vectorization Models and Feature Extractionmentioning
confidence: 99%
“…El Mostafa and Benabbou (2020) [3] made a comparative study of plagiarism detection. They concluded that most of studies are based on world granularity and use the word2vec method for word vector representation, which is their weak point, since they do not reflect the true meanings of the sentences.…”
Section: Related Workmentioning
confidence: 99%
“…Some of the existing paraphrase systems have performed quite well; however, there are certain challenges with paraphrase detection. For example, existing paraphrase systems deliver relatively good results for clean texts, but they do not perform well when applied to noisy texts [1][2][3]. Moreover, in recent years there was an expansion of deep neural network models' application to the NLP domain, and that opens up a complete new field for experimentation and improvement of the existing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…1635 extreme learning machine (ELM), and bagging classifier were among the machine learning algorithms used to define and classify credit card transaction data into fraudulent and non-fraudulent categories [11]- [14].…”
mentioning
confidence: 99%